Patterns and predictors of emergency department visits among older patients after breast cancer surgery: A population-based cohort study. Issue 3 (May 2018) - Westley, Tracy; Syrowatka, Ania; Henault, David; Rho, Young-Soo; Khazoom, Francois; Chang, Sue-Ling; Tamblyn, Robyn; Mayo, Nancy; Meguerditchian, Ari N.
Abstract: Objectives: To characterize rates, reasons for, and associated predictors for emergency department (ED) visits after breast cancer (BC) surgery. Methods: All women over 65 years undergoing curative surgery for non-metastatic incident BC (1998–2012) were identified using Quebec's universal healthcare administrative databases. Reasons for ED visits within 45 days of operation were reported. Associated factors were estimated using Cox regression. Results: Of 24, 463 patients, 12.8% had postoperative ED visits. Most frequent reasons were: superficial infection, noninfectious gastrointestinal, trauma or wound (other than breast), noninfectious respiratory, and breast wound disruption . Significant predictors included localized (aHR, 1.24, CI 1.04–1.49) or regional disease (aHR 1.64, CI 1.41–1.92), mastectomy (aHR 1.22, CI 1.10–1.34), each operation before definitive oncologic control (aHR 1.12, CI 1.03–1.21), lower institutional volume (aHR 1.23, CI 1.09–1.38), having 6–10 prescriptions (aHR 1.23, CI 1.15–1.31) or > 10 (aHR 1.53, CI 1.33–1.77), benzodiazepine use (aHR 1.09, CI 1.01–1.18), anticoagulant use (aHR 1.29, CI 1.13–1.46), cardiovascular disease (aHR 1.15, CI 1.05–1.26), diabetes (aHR 1.11, CI 1.00–1.24), past hospitalization (aHR 1.25, CI 1.17–1.34), and lower income (aHR 1.12, CI 1.04–1.20). Conclusion: Identification of risk factors in older patients before BC surgery could help prevent postoperative ED visits.